Alleviative effects of plant growth-promoting rhizobacteria on salt-stressed rice seedlings: mechanisms mediated by rhizosphere microbiota and root exudates - Wang, Jinjun; Gao, Xinru; Yang, Mingliang; Zhang, Yang; Chen, Yinglong (Frontiers in Plant Science, 2025)
IntroductionSalt stress represents a critical abiotic constraint that severely impedes plant growth and agricultural productivity. While plant growth-promoting rhizobacteria (PGPR) demonstrate potential in enhancing plant salt tolerance, their precise mechanisms remain incompletely elucidated. This study systematically investigates the mechanistic basis by which PGPR inoculation ameliorates salt stress in rice seedlings through modulation of rhizosphere microbiota and root exudate profiles.MethodsWe inoculated rice seedlings with five monocultures (Bacillus sp., Providencia sp., etc.) and a synthetic consortium (T6) under salt stress conditions. Growth parameters, rhizobacterial communities (via 16S rRNA sequencing), and root exudates (untargeted metabolomics) were comparatively analyzed against uninoculated controls (CK).ResultsPGPR inoculation significantly promoted rice seedling growth under salt stress. Treatments T2-T6 exhibited substantial increases in key biomass parameters—including root length, plant height, and dry weight—relative to the CK control. Concurrently, elevated chlorophyll content and enhanced photosynthetic efficiency were observed. Inoculated plants also displayed significantly higher activities of antioxidant enzymes (Superoxide dismutase, Peroxidase, Catalase activity) (SOD, POD, CAT) and proline (Pro) accumulation in both leaves and roots, coupled with a marked reduction in Malondialdehyde, indicating effective mitigation of oxidative damage. PGPR inoculation altered rhizosphere bacterial community composition, reducing overall alpha-diversity. Notably, the relative abundance of dominant bacterial phyla (e.g., Proteobacteria, Acidobacteriota) and beneficial genera (e.g., Subgroup_7, Lysobacter) increased significantly. These microbial shifts showed positive correlations with improved plant physiological status, suggesting a synergistic role in promoting seedling growth under salt stress. Root exudate metabolomics revealed a substantial number of differentially abundant metabolites in inoculated plants compared to CK, encompassing lipids, hormones, and signaling molecules. Crucially, the production of these specific exudates correlated with the enrichment of dominant bacterial taxa in the rice rhizosphere. Metabolic pathway analysis indicated significant enrichment primarily within Nucleotide metabolism and Purine metabolism pathways (belonging to the Metabolism superclass) and ABC transporter pathways (within Environmental Information Processing). The T6 consortium treatment induced enrichment across a significantly greater number of key metabolic pathways compared to single-strain inoculations.DiscussionPGPR inoculation enhances rice seedling growth and salt tolerance by: (1) optimizing rhizosphere microbiota (enriching dominant phyla and beneficial genera); (2) recruiting stress-mitigating microbial consortia; and (3) stimulating root exudates enriched in nucleotide/purine metabolism and ABC transporters. The superior efficacy of the T6 consortium underscores the advantage of synergistic microbial interactions. Collectively, these findings reveal plant-microbe-metabolite mechanisms underlying PGPR-mediated salt tolerance, providing a foundation for developing salinized soil remediation strategies.